Project on Strengthening Pancasila Student Profiles: Development of Traditional Early Childhood Game Modules in Kepulauan Riau - Mukhtar, Zulfadhly; Selvi, Issaura Dwi; Mukhtar AH, Nurkamelia; Tassa, Amy (JOYCED: Journal of Early Childhood Education, 2024)
This study aims to develop a traditional game module of the Kepulauan Riau as part of a project to strengthen the profile of Pancasila students in early childhood. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The results of the study indicate that this module is effective in increasing children's interest in traditional games while strengthening characters that are in line with Pancasila values such as mutual cooperation, creativity, and cultural diversity. Validation by experts shows that this module has very good feasibility. The trial was conducted in three PAUD institutions in Tanjungpinang and Bintan, with results showing positive responses from students and teachers. This module helps reduce children's dependence on gadgets and introduces them to local cultural values through games. Thus, this module can be a practical guide for teachers in learning activities to preserve traditional games and shape children's characters under the profile of Pancasila students.